The fourth COVID-19 vaccine dose increased the neutralizing antibody response against the SARS-CoV-2 Omicron (B.1.1.529) variant in a diverse Brazilian population - Jéssica Pires Farias; Robert Andreata-Santos; Ruth Dalety da Silva Brito; Milena Silva Souza; Mayanna Moreira Costa Fogaça; Josilene Ramos Pinheiro; Edgar Ferreira da Cruz; Willian Liang; Rafael da Conceição Simões; Wilson Barros Luiz; Alexander Birbrair; Paloma Oliveira Vidal; et al. (Microbiology Spectrum, 2023)
ABSTRACT Most of the original immunization regimens against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were composed of two doses, followed by a subsequent third booster dose to control the Omicron variant and hence coronavirus disease 2019 (COVID-19). However, most data generated regarding the fourth dose were not based on the general population. Therefore, this study aimed to verify the effect of the fourth COVID-19 vaccine dose in a diverse Brazilian population. This retrospective observational study was conducted between May and September 2022. We gathered data on the vaccine regimens and COVID-19 serologic status from 266 healthy volunteers who received three or four vaccine doses, as well as COVID-19 diagnosis and viral genome sequencing from 457 patients with flu-like symptoms. In addition, we conducted immunoinformatic analysis to assess the conserved epitopes in the locally circulating viruses. We showed that the fourth dose did not increase the serum levels of antiviral antibodies, as measured by enzyme-linked immunosorbent assay. However, it significantly increased neutralizing antibody (NAb) titers against the Omicron variant. All viral sequences generated in this study were Omicron subvariants, mainly B.A.5.1. Notably, most NAb epitopes present in the wild-type SARS-CoV-2 were not detected among the circulating Omicron subvariants. None of the volunteers who received the third or fourth doses presented COVID-19 for at least 1 year before the study period. Altogether, these results indicate that the fourth vaccine dose increases the serum levels of NAbs that recognize highly conserved epitopes in Omicron subvariants. IMPORTANCE Several additional COVID-19 vaccine doses were administered in the Brazilian population to prevent the disease caused by the B.1.1.529 (Omicron) variant. The efficacy of a third dose as a booster is already well described. However, it is important to clarify the humoral immune response gain induced by a fourth dose. In this study, we evaluate the effect of the fourth COVID-19 vaccine dose in a diverse Brazilian population, considering a real-life context. Our study reveals that the fourth dose of the COVID-19 vaccine increased the neutralizing antibody response against SARS-CoV-2 Omicron and significantly contributed in the reduction of the disease caused by this variant.